THE EFFECTIVENESS OF MATERIAL DESIGNING IN COMMUNICATIVE LANGUAGE TEACHING - Ziyayeva Muhayyo Usmanjanovna (Journals Park Publishing, 2022)
This paper discusses how teaching material design can contribute to educate CLT teachers to consider their prospective students' profiles. This professional activity requires the student teachers to take a set of decisions, make choices and explain the reasons for them. The author describes three different contexts of practice and presents student teacher considerations about the experiences. There are challenges and gains in the process of teaching/learning how to design ELT materials, but as has been pointed out by the activities involved in this practice the gains are worth the challenges.
Keywords: CLT, ELT, material design, syllabus, context, communicative approaches.